The global burden of colorectal cancer attributable to high body-mass index in 204 countries and territories: findings from 1990 to 2021 and predictions to 2035 - Jin, Xiaoqian; Dong, Danfeng; Xu, Zixuan; Sun, Mingming (Frontiers in Nutrition, 2024)
The association between high body-mass index (BMI) and colorectal cancer (CRC) has been confirmed and gained attention. However, a detailed understanding of the disease burden of high BMI and CRC remains lacking.Objective: This study aimed to assess the temporal and geographical trends of CRC deaths and disability-adjusted life years (DALYs) caused by high BMI globally from 1990 to 2021, providing effective guidance for developing prevention and treatment strategies.We used data from the 2021 Global Burden of Disease study to assess the global, regional, and national Deaths, DALYs, age-standardized mortality rate (ASMR), and age-standardized DALY rates (ASDR) caused by CRC related to high BMI, and further calculated the estimated annual percentage change (EAPC). We also considered factors such as gender, age, and sociodemographic index (SDI). We explore the relationship between EAPC and ASMR/ ASDR (1990) and between EAPC and SDI (2021). Further, the autoregressive integrated moving average (ARIMA) model was applied to predict the disease burden from 2022 to 2035. The risk factors were calculated by Population Attributable Fraction (PAF).